Efficacy and safety of rivaroxaban versus warfarin in the management of unusual site deep vein thrombosis: a retrospective cohort study - Fu, Linlin; Cai, Wenting; Li, Hanyang; Han, Dan; Li, Li; Wang, Baoyan (Frontiers in Pharmacology, 2024)
Background Unusual site deep vein thrombosis (DVT) was defined as venous thromboembolism (VTE) occurring outside the conventional deep veins of the lower extremity or pulmonary arteries. However, the optimal anticoagulation therapy for unusual site DVT remained unclear. This study aims to evaluate the efficacy and safety of rivaroxaban in unusual site DVT. Methods This retrospective cohort study enrolled consecutive patients at Nanjing Drum Tower Hospital between January 2011 and December 2021 who were diagnosed with unusual site DVT. Patients were divided into two groups based on their ultimate medication choice: the warfarin group and the rivaroxaban group. The demographic characteristics were recorded for all enrolled patients. Clinical outcomes included recurrent VTE, bleeding complications and major bleeding. Results A total of 1,088 patients were divided into warfarin (n = 514) and rivaroxaban (n = 574) groups. After the stabilized inverse probability of treatment weighting, Hazard Ratios for warfarin vs. rivaroxaban of recurrent VTE, bleeding complications and major bleeding were 0.52(95% CI: 0.25–1.08), 0.30(95% CI: 0.14–0.60), and 0.33 (95% CI, 0.13–0.74), respectively. Risk of clinical outcomes in specified subgroups for age, gender, renal function, thrombosis sites and diagnosis were assessed. The interaction of gender and treatment on major bleeding was significant (P for interaction = 0.062). Otherwise, there was no significant interaction between the other subgroups and the treatment group in terms of clinical outcomes. Conclusion Compared with warfarin, rivaroxaban exhibited comparable efficacy for the anticoagulant treatment of unusual site DVT, associated with a lower risk of bleeding complications and major bleeding.